RANDOMISED CONTROLLED TRIALS OF CHRONIC PAIN IN CHILDREN AND ADOLESCENTS: A SYSTEMATIC REVIEW. Issue 1 (14th December 2015) - Boulkedid, Rym; Abdou, Armiya Yousouf; Desselas, Emilie; Monegat, Marlène; Alberti, Corinne; Kaguelidou, Florentia
Abstract : Background: Approximately 15 to 30% of children and adolescents suffer from daily pain persistent over more than 3 months and there is evidence supporting that the prevalence of chronic pain is steadily increasing in this population. Chronic pain is known to have a negative impact on children's development and social behaviour, leading often to severe psychological distress and physical disability. We reviewed medical literature to assess the characteristics and quality of randomized controlled trials (RCTs) on pharmacological and non-pharmacological therapies in chronic and recurrent pain in the paediatric population. Methods: We performed a systematic search of PubMed, Embase and the Cochrane Library up to March 2014. Bibliographies of relevant articles were also hand-searched. We included all RCTs that involved children and adolescents (age 0 to 18 years) and evaluated the use of a pharmacological agent or a non-pharmacological approach in the context of chronic or recurrent pain. The latter was defined as pain persisting for more than 3 months. Methodological quality was evaluated using the Cochrane Risk of Bias Tool. Two reviewers independently assessed studies for inclusion and evaluated methodological quality. Results: A total of 52 randomized controlled trials were selected and included in the analysis. The majority were conducted in single hospital institutions, with no information on study funding. Median sample size was 45 (34–57) participants. Almost 50% of the RCTs included both adults and children with a median age at inclusion of 13 years. Non-pharmacological approaches were more commonly tested whereas evaluation of pharmacological agents concerned less than 30% of RCTs. Abdominal pain and headache were the most common types of chronic pain experienced among trial participants. Overall, the methodological quality was poor and did not parallel the number of RCTs that increased over the years. The risk of bias was high or unclear in 70% of the trials. Conclusions: This is the first systematic review of RCTs conducted to evaluate pharmacological and non-pharmacological therapies in chronic and recurrent pain in children and adolescents. Although, management of pain in adults has significantly improved over the years due to the evaluation of numerous analgesic therapies, our results highlight the existing knowledge gap with regards to children and adolescents. Therapeutic strategies, in particular pharmacological agents, applied to relieve chronic or recurrent pain in children and adolescents are not evaluated through high quality RCTs. The need to improve analgesic therapy in children and adolescents with chronic pain is still unmet. We discuss possible research constraints and challenges related to this fact as well as adequate methodologies to circumvent them.